The diagnostic role of indirect fluorescence antibody in cystic echinococcus and the role of western blot in following-up patients with cystic echinococcus after surgery - Aslan, M.; Celik, D. G.; Yuksel, PELİN; YÜKSEL MAYDA, PELİN; Saribas, S.; Cakan, H.; Abdelkareem, Ali; Bahar, H.; Ziver, T.; Yakar, H.; Kocazeybek, B. (My University, 2012)
Cystic echinococcosis (CE) is a complicated zoonotic infection with diagnosis and treatment. In this study, we aimed to determine the diagnostic performance parameters of Indirect Fluorescence Antibody (IFA) method and also the usability of Western Blot (WB) method for following up CE cases by detecting the antigenic patterns. Cases diagnosed as CE in General Surgery Department of Cerahpasa Faculty of medicine and a selected control group were included in this case-control and cross-sectional study between January 2010 and December 2010. Laboratory studies were performed in Serology/ELISA laboratory of Medical Microbiology Department. Clinically, radiologically and serologically (IHA, ELISA) diagnosed 110 patients with CE, and 80 healthy control group (HCG) individuals were included in the study. Echinococcus granulosus specific antigen IgG test was applied by IFA method in CE cases and HCG. E. granulosus specific antigen patterns were also are detected with WB method in CE cases and HCG. According to the results, performance parameters of IFA test in CE diagnosis were calculated as 100, 93, 95, 100 and 94% for sensitivity, specificity, positive predictive value, negative predictive value and Kappa values, respectively. Ninety six cases were detected positive with WB method. p7 and other accompanying bands were detected in 50 out of this 96 cases and only p39 band was detected in 45 cases. In conclusion, using IFA method in the diagnosis of CE which is a complicated infection disease can be effective in the presence of an appropriate microscope and experienced expert and we also suggest the use of WB method can be useful especially in parasitic treatment or after spontaneous cyst calcification in post-operative period.